Acute Prioritization Over Transitional Preparation: An Observational Study of Discharge Planning in the Emergency Department - Khoirotin Anisa; Alfid Tri Afandi; Dicky Endrian Kurniawan; Sujarwanto (KHD Production, 2026)
Discharge planning must commence during emergency department admission to ensure continuity of care. Ineffective transitional preparation frequently leads to patient deterioration, medication errors, and increased hospital readmissions. This study evaluated the implementation of discharge planning within the emergency department of Jember Regency Hospital. Researchers employed a descriptive cross-sectional case study design to assess nursing practices. The sample included five emergency nurses and five patients across priority levels one through three. Data collection utilized direct observation and structured Guttman-scale checklists over five days. Findings revealed optimal execution during the initial patient admission phase, specifically regarding comprehensive healthcare needs assessment and interprofessional collaboration. Conversely, the preparatory phase exhibited significant clinical deficiencies, particularly in patient education concerning activity regulation, medication adherence, and dietary management. Critical patients prioritized for immediate life-saving interventions frequently bypassed these educational components. The final discharge and transfer phases demonstrated high compliance with logistical protocols, including medical order verification and transportation coordination. Systemic barriers, including high patient acuity, unpredictable emergency workflows, and the absence of standardized documentation templates, severely restricted comprehensive educational interventions. Emergency discharge planning requires urgent structural reforms to integrate proactive patient education directly into acute care workflows. Hospitals must develop standardized electronic protocols to enhance nursing standards, reduce preventable readmissions, and ensure seamless continuity of care across all patient priority levels.